Correspondence analysis - Michal Benko; Michel Lejeune (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Correspondence analysis (CA) is a descriptive method which allows us to analyze and to XploRe the structure of contingency tables (or, by extension, non-negative tables where rows and columns are the entities of interest). It is similar to principal cornponent analysis (PCA) in the sense that, it attempts to obtain a representation of either the I row items or the J column items in a low dimensional space, while preserving at best total variation in the table.
urn:nbn:de:kobv:11-10047907
Keywords: 330